Exploring Music Teaching Methods Through Core Literacy: A Deep Learning Approach with Implications for Cognitive and Emotional Development in Sports - Yajie Shi, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Core literacy encompasses the essential skills and abilities students need to effectively adapt to and thrive in society. Developing core literacy during the teaching stage is a critical component of implementing moral and holistic education in schools. In the context of music education, a teaching model centered on core literacy is vital for enhancing the overall quality of instruction and fostering deeper cognitive and emotional engagement. This study explores music teaching methods through the lens of core literacy, utilizing deep learning approaches to reform traditional teaching practices. Deep learning encourages students to go beyond the simple application of knowledge points, enabling them to apply their music knowledge to solve complex problems in dynamic learning environments crafted by teachers. This paper examines the potential of these methods to improve music education quality, emphasizing the integration of cognitive, emotional, and collaborative skills. In the context of sports psychology, these findings highlight parallels between music and sports education. Both disciplines benefit from strategies that promote critical thinking, emotional resilience, and teamwork. By applying these principles, educators can foster holistic development, enhance performance, and support lifelong learning in both music and sports settings. This research aims to inspire innovation in teaching methods for those invested in educational reform.